Suitable glass-ceramic sealant for planar solid-oxide fuel cells - Sohn, SB; Choi, SY; Kim, GH; Song, HS; Kim, GD (AMER CERAMIC SOC, 2004)
Various glass-ceramics were prepared based on the BaO-Al2O3-B2O3-SiO2 system with the addition of La2O3, ZrO2, or NiO in an attempt to develop a suitable sealant for planar solid-oxide fuel cells operating at 800degreesC. To estimate the applicability of these glasses as suitable sealants, their thermal and chemical stabilities as well as the crystallization behavior and bonding characteristics of their parent glasses were investigated. The thermal properties and crystallization behavior of the parent glasses were dependent on the type of additive used, and the bonding characteristics were strongly influenced by the B2O3/SiO2 value in the glass composition. Observation of microstructural change and chemical reaction at the glassceramic/electrolyte interface confirmed that the prepared glass-ceramics possessed long-term stability during heat treatment at the operation temperature for up to 1000 h.
Keywords: SEALING MATERIALS; SOFC